Thermo-economic analysis of a novel P2X polygeneration system for hydrogen, ammonia, and methanol production with near-zero emissions - Laveet Kumar (11460088) (2025)
This paper presents a comprehensive thermo-economic analysis of a novel Power-to-X (P2X) polygeneration system designed for the production of hydrogen, ammonia, and methanol with near-zero CO2 emissions. The system integrates an air separation unit (ASU), a direct oxy-combustor (DOC) powered by natural gas, combined with a supercritical carbon dioxide (sCO2) power cycle, water electrolyzer (WE), a Haber-Bosch process (HBP), and a methanol production unit (MPU). The system is investigated in four configurations: ASU + DOC-sCO2 (S1), ASU + DOC-sCO2 + WE (S2), ASU + DOC-sCO2 + WE + HBP (S3), and ASU + DOC-sCO2 + WE + HBP + MPU (S4), each contributing to improve energy efficiency and reduced emissions. Simulation results show that the overall system efficiency reaches 56 %, improving from 45 % to 56 % across different configurations. The system's levelized cost of hydrogen (LCOH) decreases significantly from $1.70/kg to $0.80/kg, and the levelized cost of electricity (LCOE) decreases from 4.30 ¢/kWh to 3.30 ¢/kWh. CO2 emissions are reduced from 200 gCO2/MWe to 145 gCO2/MWe, with the CO2 reduction rate improving from 89 % to 94 %. These results demonstrate the economic viability and environmental sustainability of the proposed P2X system paving the way for industrial decarbonization and large-scale deployment in future energy infrastructures. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2025.150201